2012
DOI: 10.1093/icvts/ivs472
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracic surgery versus open thoracotomy for non-small cell lung cancer: a meta-analysis of propensity score-matched patients

Abstract: In view of a paucity of high-level clinical evidence in the form of large, well-designed randomized controlled trials, propensity score matching may provide the highest level of evidence to compare VATS with open thoracotomy for patients with NSCLC. The present meta-analysis demonstrated superior perioperative outcomes for patients who underwent VATS, including overall complication rates and duration of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(109 citation statements)
references
References 25 publications
1
102
1
5
Order By: Relevance
“…VATS has the advantage of providing an improved visual field and cosmesis. Previous studies have verified that VATS has other advantages, such as a lower concentration of inflammatory cytokines (20), a lower risk of developing chest infection, reduced pain and improved lung function (21,22). An increasing body of evidence has indicated that patients undergoing VATS experience a shorter hospital stay, have their chest tubes removed earlier (23,24) and have an improved prognosis (25).…”
Section: Discussionmentioning
confidence: 97%
“…VATS has the advantage of providing an improved visual field and cosmesis. Previous studies have verified that VATS has other advantages, such as a lower concentration of inflammatory cytokines (20), a lower risk of developing chest infection, reduced pain and improved lung function (21,22). An increasing body of evidence has indicated that patients undergoing VATS experience a shorter hospital stay, have their chest tubes removed earlier (23,24) and have an improved prognosis (25).…”
Section: Discussionmentioning
confidence: 97%
“…5,20,[58][59][60][61] The level of cardiac risk that a patient presents also can guide the type of surgery selected and may favor less invasive interventions, such as VATS and RATS, that generally are correlated with lower rates of overall perioperative morbidity in terms of pneumonia and atrial arrhythmia. [64][65][66] Thanks to these advances in surgical care, morbidity and mortality rates after lung resection have decreased significantly over time. The current rates of mortality, as reported by the Society of Thoracic Surgeons and the European Association of Cardio-Thoracic Surgery, are between 1.6% to 2.3% after lobectomy and 3.7% to 6.7% after pneumonectomy.…”
Section: Surgical Perspectivementioning
confidence: 99%
“…In one study involving propensityscore-matched patients, VATS lobectomy was associated with no significant difference in mortality, but with significantly lower rates of overall perioperative morbidity, pneumonia, and atrial arrhythmia. 34 Recommendations on the selection of surgical approach and its impact on risk …”
Section: Endovascular Vs Open Vascular Proceduresmentioning
confidence: 99%